DAMPAK KONVERSI LAHAN PETANIAN TERHADAP KONDISI SOSIAL EKONOMI PETANI DI KECAMATAN TIKUNG KABUPATEN LAMONGAN - Pramudiana, Ika Devy (P3M IAIN KEDIRI, 2017)
Conversion of agricultural land resulted in socio-economic changes for farmers who do the conversion, which would then have an impact on the level of well-being of farmers. The methods used in the writing of this research is qualitative research methods. The result of the writing of this library study revealed that land conversion Conditions farmers â livelihood before and after the existence of the land conversion is seen in terms of revenue is the amount of income of farmers after the land conversion there is increased and decreased from the amount of income before the existence of land conversion. The condition of the housing and kepemilikikan assets havenât changed much both before and after the existence of land conversion. At this writing specified on conversion of agricultural land, livelihoods, economic conditions, the income of farmers, and its impact on the level of household well-being of farmers in the countryside. Keywords: land conversion, social change, wellbeing